Diversity of use and local knowledge of wild and cultivated plants in the Eastern Cape province, South Africa - Alfred Maroyi (BMC, 2017)
Abstract Background Traditional ecological knowledge among indigenous communities plays an important role in retaining cultural identity and achieving sustainable natural resource management. Hundreds of millions of people mostly in developing countries derive a substantial part of their subsistence and income from plant resources. The aim of this study was to assess useful plant species diversity, plant use categories and local knowledge of both wild and cultivated useful species in the Eastern Cape province, South Africa. Methods The study was conducted in six villages in the Eastern Cape province, South Africa between June 2014 and March 2017. Data on socio-economic characteristics of the participants, useful plants harvested from the wild, managed in home gardens were documented by means of questionnaires, observation and guided field walks with 138 participants. Results A total of 125 plant species belonging to 54 genera were recorded from the study area. More than half of the species (59.2%) are from 13 families, Apiaceae, Apocynaceae, Araliaceae, Asparagaceae, Asphodelaceae, Asteraceae, Fabaceae, Lamiaceae, Malvaceae, Myrtaceae, Poaceae, Rosaceae and Solanaceae. More than a third of the useful plants (37.6%) documented in this study are exotic to South Africa. About three quarters of the documented species (74.4%) were collected from the wild, while 20.8% were cultivated and 4.8% were spontaneous. Majority of the species (62.4%) were used as herbal medicines, followed by food plants (30.4%), ethnoveterinary medicine (18.4%), construction timber and thatching (11.2%). Other minor plant use categories (1-5%) included firewood, browse, live fence, ornamentals, brooms and crafts. Conclusion This study demonstrated that local people in the Eastern Cape province harbour important information on local vegetation that provides people with food, fuel and medicines, as well as materials for construction and the manufacturing of crafts and many other products. This study also demonstrated the dynamism of traditional ecological knowledge, practices and beliefs of local people demonstrated by the incorporation of exotic plants in their diets and indigenous pharmacopoeia.